Effect of vitrification and slow freezing on in-vitro matured prepubertal goat oocytes - SINHA, RAJNI; KHARCHE, S D; SINHA, N K; GOEL, A K; JINDAL, S K; SARASWAT, SONIA (The Indian Journal of Animal Sciences, 2014)
The present study was conducted to study the post thaw recovery rate of morphologically normal matured oocytes subjected to vitrification and slow freezing method. Oocytes were matured in TCM-199, which comprises sodium pyruvate (0.25 mM), L- glutamine (1 mg/10 ml), gentamycin (50 μg/ml) and supplemented with 10% fetal bovine serum at 38.5°C in CO2 incubator under humidified air. After 27 h of in-vitro maturation oocytes were assigned for freezing, viz. vitrification, slow cooling and control cooling. The percentage of oocytes recovered after thawing was significantly higher for control than those for vitrification (69.67%) and slow freezing (85.00%), respectively. Moreover, the cleavage rate in vitrification, slow freezing and control were 1.14, 3.92 and 13.37%, respectively. Thus, the cleavage rate of oocytes in vitrification and slow freezing method did not differ significantly. However, there was a significant difference in cleavage rates of freezing groups and the control groups.